Social Practices and Dynamic Non-Humans Nature, Materials and Technologies - Maller, Cecily; Strengers, Yolande; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The robots are coming! So too is the 'age of automation', the march of 'invasive' species, more intense natural disasters, and a potential cataclysm of other unprecedented events and phenomena of which we do not yet know, and cannot predict. This book is concerned with how to account for these non-humans and their effects within theories of social practice. In particular, this provocative collection tackles contemporary debates about the roles, relations and agencies of constantly changing, disruptive, intelligent or otherwise 'dynamic' non-humans, such as weather, animals and automated devices. In doing so contributors challenge and take forward existing understandings of dynamic non-humans in theories of social practice by reconsidering their potential roles in everyday life. The book will benefit sociology, geography, science and technology studies, and human- (and animal-) computer interaction design scholars seeking to make sense of the complex entanglement of non-human phenomenaand things in the performance of social practices.
Chapter 1 Dynamic non-humans in a changing world -- PART I: Nature, materiality and processes -- Chapter 2 Thriving in the Anthropocene: understanding human-weed relations and invasive plant management using theories of practice -- Chapter 3 Seeing wood for the trees: placing biological processes within practices of heating and harvesting -- Chapter 4 'Dynamic' non-human animals in theories of practice: views from the subaltern -- Chapter 5 Dynamic bodies in theories of social practice: vibrant materials and more-than-human assemblages -- Chapter 6 Mobile drinking - bottled water practices and ontological politics -- Chapter 7 Immersed in thermal flows: heat as productive of and produced by social practices -- PART II: Technologies, automation and performativity -- Chapter 8 Displacement: attending to the role of things in theories of practice through design research -- Chapter 9 How software matters: connective tissue and self-driving cars -- Chapter 10 Automated artefacts as co-performers of social practices: washing machines, laundering and design -- Chapter 11 Robots and Roomba riders: non-human performers in theories of social practice -- Chapter 12 Automation, smart homes and symmetrical anthropology: non-humans as performers of practices?.
Keywords: Human geography; Environmental sciences -- Social aspects; Science -- Social aspects; Social sciences -- Philosophy; User interfaces (Computer systems).; Human-computer interaction; Human Geography; Environmental Social Sciences; Science and Technology Studies; Social Theory; User Interfaces and Human Computer Interaction